Performance improvement of charge trap flash memory by using a composition-modulated high-k trapping layer - 汤振杰 李荣 殷江 (Chinese physics B, 2013)
A composition-modulated （HfO2）x（Al2O3）1-x charge trapping layer is proposed for charge trap flash memory by controlling the A1 atom content to form a peak and valley shaped band gap. It is found that the memory device using the composition-modulated （HfO2）x（Al2O3）l-x as the charge trapping layer exhibits a larger memory window of 11.5 V, improves data retention even at high temperature, and enhances the program/erase speed. Improvements of the memory characteristics are attributed to the special band-gap structure resulting from the composition-modulated trapping layer. Therefore, the composition-modulated charge trapping layer may be useful in future nonvolatile flash memory device application.